2018
DOI: 10.1161/jaha.117.006656
|View full text |Cite
|
Sign up to set email alerts
|

Sphingolipid Metabolic Pathway Impacts Thiazide Diuretics Blood Pressure Response: Insights From Genomics, Metabolomics, and Lipidomics

Abstract: BackgroundAlthough hydrochlorothiazide (HCTZ) is a well‐established first‐line antihypertensive in the United States, <50% of HCTZ treated patients achieve blood pressure (BP) control. Thus, identifying biomarkers that could predict the BP response to HCTZ is critically important. In this study, we utilized metabolomics, genomics, and lipidomics to identify novel pathways and biomarkers associated with HCTZ BP response.Methods and ResultsFirst, we conducted a pathway analysis for 13 metabolites we recently ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 61 publications
1
15
0
1
Order By: Relevance
“…In rodents, sphingomyelin supplementation has been shown to help reduce the intestinal absorption of serum lipids such as cholesterol and triglycerides [12]. Sphingomyelin levels have also been associated with mild-to-moderate hypertension [29]. Based on these findings, supplementation could be an avenue to explore in the context of dyslipidemia in type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…In rodents, sphingomyelin supplementation has been shown to help reduce the intestinal absorption of serum lipids such as cholesterol and triglycerides [12]. Sphingomyelin levels have also been associated with mild-to-moderate hypertension [29]. Based on these findings, supplementation could be an avenue to explore in the context of dyslipidemia in type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Of great importance is the coupling of the genome and metabolome to inform about treatment outcomes. This is a concept referred to as pharmacometabolomics informs pharmacogenomic', which was applied initially to the study of antidepressants [88,89] and then enlarged to the study of many drug classes [75,76,90]. Here, information from both baseline and the change in metabolism was able to benefit from and add to information derived from the genome [18,88,91].…”
Section: Pmx Data and Pgx Datamentioning
confidence: 99%
“…In the last decade, PMx has shown the ability to improve predictions when combined with PGx [18,88,90,120]. The concept that "pharmacometabolomics informs pharmacogenomics" is now being tested in many clinical centers.…”
Section: Where We Are Today and The Future Of Pmxmentioning
confidence: 99%
“…In terms of baseline protein expression in responders and nonresponders, responders had greater mRNA baseline levels of a number of proteins including vasodilator-stimulated phosphoprotein (VASP) and metabolites of the sphingolipid metabolic pathway (Turner et al, 2013; Shahin et al, 2017; Sá et al, 2018). It was suggested that increased baseline VASP expression and the sphingolipid metabolic pathway were responsible for TZD efficacy of arterial blood pressure reduction (Shahin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The involvement of these pathways in TZD reduction of arterial pressure warrants additional investigation. Indeed, it remains unclear whereby, e.g., increased sphingolipid metabolism would result in greater efficacy of TZD reduction of arterial pressure (Shahin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%